Pengaruh Lingkungan Kerja, Budaya Kerja, Dan Pengembangan Karir Terhadap Kinerja Karyawan Hotel Kurnia Bengkulu Utara. - Muhammad Bintang Azhari; Fauzan Fauzan; Janusi Waliamin (Jurnal Mirai Management, 2023)
This study aims to determine how much influence the Work Environment (X1) Work Culture (X2) and Career Development (X3) have on Employee Performance (Y) Hotel Kurnia Bengkulu Utara. By using the Likert scale method by distributing questionnaires to respondents. The method used in this research is explanatory research". The population of this study were all employees of Hotel Krunia Bengkulu Utara, 30 samples using the saturated sample method. The analytical tool used in this research uses SPSS 22. The data analysis method used is multiple linear regression analysis. The results of the study show that (1) "Work Environment (X1) has a significantly positive effect on Employee Performance Satisfaction (Y). (2) Work Culture (X2) has a significant negative effect on Employee Performance (Y). (3) Career Development (X3) has no significant negative effect on Employee Performance (Y). (4) Work Environment (X1) Work Culture (X2) and Career Development (X3) have a significant effect on Employee Performance (Y). keywords: Work Environment, Work Culture, Career Development, Employee Performance